2001
DOI: 10.1002/biof.5520140130
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of selenium‐contaminated sediments and water

Abstract: Selenium (Se) is a contaminant of agricultural irrigation-drainage water in the western United States, and the cause of wildlife deaths and grotesque deformities. Some approaches in reducing the toxic Se concentrations from contaminated sediments and water have been proposed, but most of these tend to be costly or ineffective. Bioremediation through microbial transformations of toxic Se species into nontoxic forms is being considered as an effective remedial alternative. The microbial reduction of toxic oxyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…fungal strains (Srivastava et al, 2011). These results not only proposed the application of fungi cultivation for As removal and bioremediation, also supposed that the amount of released arsines from soils, sediments and waters by indigenous fungi may be enhanced by the optimization of environmental parameters affecting volatilization, such as the addition of soil nutrients and moisture and aeration regulation (Thompson-Eagle et al, 1989;Frankenberger and Arshad, 2001). …”
Section: Microorganisms Capable Of Volatilizing As 21 Fungimentioning
confidence: 99%
“…fungal strains (Srivastava et al, 2011). These results not only proposed the application of fungi cultivation for As removal and bioremediation, also supposed that the amount of released arsines from soils, sediments and waters by indigenous fungi may be enhanced by the optimization of environmental parameters affecting volatilization, such as the addition of soil nutrients and moisture and aeration regulation (Thompson-Eagle et al, 1989;Frankenberger and Arshad, 2001). …”
Section: Microorganisms Capable Of Volatilizing As 21 Fungimentioning
confidence: 99%
“…Microbial volatilization opens perspectives for recovering selenium via the gas phase, which is thus free from cells and other metal contaminants. For a long time, microbial volatilization was considered a slow process (129,130,(133)(134)(135) that was unsuitable for industrial applica- , and heavy metals from wastewater or process water. In the BSer process, SeO 4 2Ϫ and SeO 3 2Ϫ are reduced to elemental selenium by biofilms of propriety microorganisms, using molasses as the carbon source and electron donor (117).…”
Section: ϫmentioning
confidence: 99%
“…The central valley of California has a notorious problem with Se buildup in ponds in wetlands in the area, which have proven to be toxic for local wildlife. Studies by Terry et al ((DE SOUZA et al 2001)) and Frankenberger et al (FRANKENBERGER and ARSHAD 2001;FRANKENBERGER and KARLSON 1994;FRANKENBERGER and KARLSON 1995) demonstrated that from 30 to 70% of the Se coming into the wetlands are volatilized. Microalgae and bacteria were shown to be responsible in a number of studies that added fungicides and bacteriocides to the wetlands water.…”
Section: Volatilizationmentioning
confidence: 99%